Colonic Diffuse Large B-Cell Lymphoma in a Liver Transplant Patient with Historically Very Low Tacrolimus Levels - Christopher M. Moore; Ihab Lamzabi; Anne K. Bartels; Shriram Jakate; David H. Van Thiel (Case Reports in Transplantation)
Posttransplant lymphoproliferative disorders (PTLDs) comprise a wide spectrum of hematologic malignancies that are found increasingly in orthotopic liver transplant (OLT) patients given the rising frequency of these surgeries and their long-term success. PTLDs are highly correlated with both the Epstein-Barr virus (EBV) infection and the degree of immunosuppression involved. Herein is reported a case of a 53-year-old male with successfully treated hepatitis C virus genotype 4 and hepatocellular carcinoma who underwent OLT and developed symptoms of weakness and poor appetite 4 years later while on tacrolimus 3 mg b.i.d. with historically very low plasma levels. He was found to be anemic and colonoscopy revealed a 4.5 cm cecal diffuse large B-cell lymphoma (DLBCL). Further workup revealed mesenteric lymph node enlargement consistent and nodal DLBCL dissemination. He was treated with cyclophosphamide-hydroxyldaunorubicin-oncovin-prednisone-rituximab (CHOP-R) chemotherapy and his tacrolimus dose was lowered. Additionally, he manifested PTLD-associated cryoglobulinemia leading to acute kidney injury. After a prolonged hospitalization he was discharged with close followup.